The behaviour of high-rise building with or without shear wall under different earthquakes - M. A., Amzar Kamarudin; S. W., Ahmad; W. A. R., Wan Ariffin (Penerbit UMP, 2021)
On the 5th June 2015, an earthquake hit Ranau, Sabah with a magnitude of 6.0 that caused 18 casualties and several injuries are one of the examples that show Malaysia is not safe from any seismic event. Most of the structure in Malaysia was designed not to include seismic action. Furthermore, an area that has a high density of population such as in the central region (Klang valley) and several main cities in Malaysia has less available land to build landed housing and uses high-rise apartments as an alternative. High-rise buildings that are normally having problems with soft story mechanisms and plan irregularity which could lead to severe damage when earthquakes happen. This study aims to observe the response of high-rise buildings when under different earthquakes in the presence of shear walls. To achieve this objective two models were modelled and analyzed by using ETABS software, the one with a shear wall and the one with no shear wall. The methods used in this study were the response spectrum method and time-history analysis. In the end, the parameters observed were base shear, story stiffness, story drift, and story displacement. The observations highlighted that the effect of earthquake intensities shows a significant effect. The acquired results indicated that the building with the shear wall is more resistant and strong structures as compared to buildings without shear wall when undergoing seismic analysis.